Land lease in Slovakia in the light of the new legal regulations - Lazíková, Jarmila; Bandlerová, Anna (Przegląd Prawa Rolnego, 2022)
Agricultural land plays an important role in national food sovereignty where agricultural producers play a dominant role. Therefore the objective of Slovak lawmakers is to create conditions enabling agricultural land to remain in the hand of farmers. The Act on Land Lease is one of the most important legal regulations in the Slovak Republic where most of agricultural land is leased by agricultural producers. The paper identifies the main legal institutions of land lease in Slovakia and discusses the balanced relationships between a lessor as a landowner and a lessee as an agricultural producer and the relationship between them and their legal certainty in this relationship, mainly in situations when they rely on legal regulations that do not specify directly and explicitly their rights and obligations arising from land lease contracts. The most recent important amendments to land law are also discussed and some necessary modifications aimed at clarifying the relationship between parties to a lease contract are proposed.